PERFORMANCE OF NILE TILAPIA FED DIETS CONTAINING MEAL RADISH FORAGE - Dos Santos, Vivian Gomes [UNESP]; Fernandes Junior, Ademir Calvo [UNESP]; Koch, João Fernando Albers [UNESP]; Barros, Margarida Maria [UNESP]; Guimarães, Igo Gomes [UNESP]; Pezzato, Luiz Edivaldo [UNESP] (My University, 2009)
Alternative protein sources have been studied in order to reduce feed costs. In a completely random experimental design (five treatments and six replicates) 180 Nile tilapia fingerlings were distributed in 30 aquaria (50 L). The fish were fed isoprotein (28% digestible protein) and isoenergetic (3000 kcal digestible energy kg-1) diets where soybean meal was substituted by fodder radish meal at the following levels: 0, 12.5, 25, 50 and 75%. Performance and chemical composition of the fillet were determined after 90 days. It was conclude that fodder radish meal can substitute soybean meal up to 25% without any interference on performance and fillet composition of Nile tilapia fingerlings.
DESEMPENHO PRODUTIVO DA TILÁPIA-DO-NILO ARRAÇOADA COM DIETA CONTENDO FARELO DE NABO FORRAGEIRO
Keywords: Oreochromis niloticus; Performance; Raphanus sativus